Enigmatic Entities of the Acellular World: Viruses, Viroids, and Virusoids - Sidhant Jain; Soumen Das (European Journal of Biology)
Genetic material confined within the lipid based cellular boundaries was earlier considered synonymous with life. However, with the discovery of viruses in late 19th century, the existence of acellular biological entities was established. Viruses, viroids, and virusoids are unique entities which have different relationships with different life forms ranging from mutualistic to parasitic ones. These entities provide evidence in support of the idea of ‘RNA world’ in the origin of life on Earth. In the present time, viruses are relatively well studied but the same cannot be said for viroids and virusoids. There has been a growing focus on the impact of these entities, in terms of human welfare as well as their impact on susceptible varieties of plants. As a result, studying their origin, evolution and pathogenicity has become a subject of the uttermost importance. In this review, we have discussed different facets of viruses, viroids and virusoids like their historical background, classification and mode of entry and replication in the host. We have also summarized various possible theories on their origin and evolution and have provided our take on it. This work indicates the possibility that different viruses originated distinctly by utilizing different strategies and evolved further. Clues like small size and high GC content in genomes indicate that viroids must be an important component of the pre-cellular world and it is possible that they might have originated before viruses. Furthermore, as viroids and virusoids show certain conserved properties, it suggests a probable link between them.